2010
DOI: 10.1093/ndt/gfq089
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor-23 (FGF-23) is independently correlated to aortic calcification in haemodialysis patients

Abstract: In haemodialysis patients, FGF-23 and ACI were significantly increased, and FGF-23 was independently associated with aortic calcification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
113
1
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(142 citation statements)
references
References 32 publications
13
113
1
8
Order By: Relevance
“…Nasrallah et al [13], found that Fibroblast growth factor-23 (FGF-23) is independently correlated to aortic calcification in haemodialysis patients. A reasonable explanation for this phenomenon is that FGF-23 may cause thickening and fibrosis of the carotid intima by binding to its receptor [14].…”
Section: Discussionmentioning
confidence: 99%
“…Nasrallah et al [13], found that Fibroblast growth factor-23 (FGF-23) is independently correlated to aortic calcification in haemodialysis patients. A reasonable explanation for this phenomenon is that FGF-23 may cause thickening and fibrosis of the carotid intima by binding to its receptor [14].…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown whether elevated serum FGF-23 regulates urinary phosphate excretion in dialysis patients. On the contrary, recent data have established a relationship between high levels of FGF-23 and increased mortality and vascular calcifications in hemodialysis patients (9,10). However, the mechanism is unclear.…”
Section: Introductionmentioning
confidence: 98%
“…These facts suggest that FGF23 may have a protective effect on vascular calcification by hyperphosphatemia suppression. In contrast, several hemodialysis studies reported that elevated FGF23 levels were associated with aortic calcification (6) and mortality (7,8) independent of serum phosphorus levels. Elevated serum FGF23 levels, even within the normal range, are reportedly associated with increased left ventricular mass index and increased risk for the presence of left ventricular hypertrophy in elderly subjects (9).…”
mentioning
confidence: 93%